EFIKASI DIRI SEBAGAI FAKTOR KEBERHASILAN DALAM PSIKOLINGUISTIK - Putri Schatzi Abdillah; Nisfi Alfitriani; Fitria Annisa Muhtar; Muhammad Prasetyo Nugroho; Iis Lisnawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to examine the role of self-efficacy as a determinant of success in the field of psycholinguistics. Self-efficacy, which refers to an individual's belief in their ability to complete a particular task, has a significant impact on the process of language acquisition, comprehension, and production. Through a literature study method by analyzing several relevant scientific articles from various leading national journals, this study identified that self-efficacy has a positive effect on language ability, language learning motivation, and communication performance. The results of the study indicate that individuals with high levels of self-efficacy tend to have more effective language learning strategies, resilience in facing linguistic difficulties, and better achievement in language tasks. These findings underline the importance of developing self-efficacy in the context of language learning and psycholinguistic interventions, and provide practical implications for educators, psychologists, and linguists in designing programs that facilitate the improvement of linguistic abilities.